Metabolic Abnormalities in a Cohort of Overweight and Obese Children in an Urban Setting of Sri Lanka - Loretta S. Warnakulasuriya; Dulani L. Samaranayake; Adikaram V. N. Adikaram; Manel M. A. Fernando; Elisabet Rytter; Iris Ciba; Peter Bergsten; Anders H. Forslund; K. D. Renuka Ruchira Silva; Vithanage Pujitha Wickramasinghe (International Journal of Endocrinology)
Childhood obesity-related metabolic derangements are increasing among South Asian populations. Most of these changes persist to adulthood. This study aims to describe the distribution of metabolic abnormalities among 7- to 17-year-old overweight and obese children in the Gampaha District of Sri Lanka. Overweight children (age- and gender-adapted BMI>+1SD, WHO standards) were selected from a community survey carried out in the Negombo Education Zone of Gampaha District. After a 12-hour overnight fast, blood was drawn, and blood glucose (FBG), lipid profile, insulin, and liver transaminases were measured. Two hours after a glucose load, blood was drawn for random blood glucose (RBG) and insulin. Metabolic syndrome (MetS) was diagnosed using modified IDF criteria for children. Anthropometry, fat mass (FM), and blood pressure were measured. Hepatic fat pattern was assessed ultrasonically. The data of 403 children (210 boys) were analysed. Of the study population, 16.4% were overweight (BMI for age +1 to +2SD), 72% were obese (BMI for age >+2 to +3SD), and 11.6% were severely obese (BMI for age >+3SD). Insulin resistance was seen in 46.8%, and prevalence increased with age. Mean postprandial insulin ranged from 368 to 625 pmol/L and was elevated in 35%. Dysglycaemia was seen among 20.8%. MetS was present in 19.8%, and 84% had at least one metabolic abnormality. Different degrees of hepatic steatosis were observed in 32.5%, and elevated ALT/AST ratio was seen in 58% of the population. Overweight and obesity during childhood were associated with multiple metabolic abnormalities including MetS, and they occur from a young age. It is important to screen children for overweight/obesity early in life and intervene to prevent them from developing metabolic complications.